علاقة التوافق النفسي بتقييم أساتذة التربية البدنية وفق المقاربة بالكفاءات لدى تلاميذ السنة الرابعة في امتحان شهادة التعليم المتوسط دورة ماي 2015. - لخضر, سالم; معوش, عبد الحميد; عمرون, سليم (Université de M'sila, 2015)
هدفت الدّراسة الحالية إلى التعرف على التّوافق النّفسي وعلاقته بتقييم أساتذة التعليم المتوسط لدى تلاميذ السّنة الرابعة المتوسط، وذلك بالإجابة على التّساؤلات التالية: ما مستوى التّوافق النّفسي لتلاميذ السّنة الرابعة المتوسط عينة الدراسة؟، هل توجد علاقة دالّة إحصائيا بين التّوافق النّفسي وتقييم أساتذة التعليم المتوسط لدى عيّنة من تلاميذ السّنة الرابعة المتوسط؟، هل توجد فروق ذات دلالة إحصائية بين الإناث والذّكور في التوافق النفسي لدى أفراد عيّنة الدّراسة؟ وكانت عيّنة الدّراسة النّهائية عبارة عن (47) تلميذا من تلاميذ السّنة الرابعة المتوسط، حيث (22) تلميذا من الذّكور و (25) تلميذة من الإناث. وتمّ استعمال أدوات الدّراسة كالتالي: استبانة التوافق النفسي من إعداد الباحثين، ونتائج امتحان شهادة التعليم المتوسط في مادة التربية البدنية ماي 2015. وتمّ استعمال مجموعة من الأساليب الإحصائية: كالنّسب المئوية والمتوسّطات والانحرافات المعيارية والترتيب ومعامل الارتباط بيرسون واختبار الفروق (T- test)، وجاءت نتائج الدّراسة كالتّالي: مستوى التّوافق النّفسي لتلاميذ السّنة الرابعة المتوسط عينة الدراسة متوسط، توجد علاقة دالّة إحصائيا بين التّوافق النّفسي وتقييم أساتذة التعليم المتوسط لدى عيّنة من تلاميذ السّنة الرابعة المتوسط، لا توجد فروق ذات دلالة إحصائية بين الإناث والذّكور في التّوافق النّفسي الكلّي لدى أفراد عينّة الدّراسة. Abstract: The present study aimed to identify the psychological adjustment and its relationship to evaluate the professors average education of students of the fourth year average, and by answering the following questions: - What psychological adjustment for students of the fourth year the average level of the study sample? - Is there a statistically significant relationship between psychological adjustment and evaluation of intermediate education professors among a sample of students of the fourth year average? - Are there significant differences between females and males in psychological adjustment for the study sample? The final study sample is a (47) students from the fourth year students of the medium, where (22) of male students and 25 female student. The study was the use of tools as follows: - Identify the psychological adjustment of the preparation of researchers. - The results of middle school certificate exam in physical education May 2015. It was the use of a set of statistical methods: percentages and averages and standard deviations, arranging, and Pearson correlation coefficient test for differences (T- test ... ( The results of the study are as follows: - Psychological adjustment for the students of the fourth year average sample of the study average level. - No statistically significant relationship between psychological adjustment and evaluation of intermediate education professors among a sample of students of the fourth year average. - There were no statistically significant differences between females and males in psychological adjustment to the total study sample.
Keywords: التوافق النفسي أساتذة التربية البدنية المقاربة بالكفاءات تلاميذ السنة الرابعة امتحان شهادة التعليم المتوسط